An exploration of social systems as informative for urban regeneration in Potchefstroom Central Business District - Puren, Karen; Meiring, Gert (Department of Urban and Regional Planning, University of the Free State, 2015)
The future of cities undoubtedly spells change on many levels due to urban growth. One of the mechanisms used in cities to cope with change is urban regeneration. Urban regeneration has mainly been addressed through economic and planning policies geared towards physical renewal, with hardly any understanding or acknowledgment of the social dynamics underlying the physical process. Social dynamics are important to consider in urban regeneration, as they form the underlying driving forces of cities. However, little is known about these underlying forces. The aim of this research is to explore the role of social systems in the Central Business District of Potchefstroom. An ethnographical approach is used to guide the methodology, while qualitative methods (observations and interviews) are used to capture data about the social systems that are present in the study area, how these social systems interact with one another, and how they can be included in urban regeneration initiatives. The findings suggest the existence of three interactive social systems that reflect pro-social behaviour and cultural relativism which, in turn, create vitality in the study area. Social systems play a multi-levelled role in the study area. Their role can possibly inform urban regeneration by being proactive in terms of attracting new and maintaining existing social relationships; being creative in terms of adapting and changing the physical environment to address needs, and being supportive in order to unlock internal resources such as local knowledge, creativity, commitment, energy and ownership.

Die toekoms van stede voorspel ongetwyfeld veranderings op vele vlakke as gevolg van verwagte stedelike groei. Een van die meganismes wat aangewend word in stede ten einde veranderings te kan hanteer, is stedelike regenerasie. Stedelike regenerasie is in die verlede hoofsaaklik aangespreek deur ekonomiese en beplanningsbeleide wat gerig was op fisiese hernuwing, met min begrip of inagneming van die sosiale dinamiek wat die proses onderlê. Sosiale dinamika is belangrik om te oorweeg in stedelike regenerasie omrede dit die onderliggende dryfkrag van stede is. Min kennis is egter beskikbaar aangaande hierdie onderliggende kragte. Die doel van hierdie navorsing is om ondersoek in te stel na die rol van sosiale sisteme in die Sentrale Sakekern van Potchefstroom. ‘n Etnografiese benadering is gebruik om die metodiek te rig, terwyl kwalitatiewe metodes (waarnemings en onderhoude) gebruik is om data te versamel aangaande die sosiale sisteme wat teenwoordig is in die studiegebied, die aard van die interaksie tussen hierdie sosiale sisteme en hoe die sisteme in stedelike regenerasie ingesluit kan word. Die bevindinge dui op die teenwoordigheid van drie interafhanklike sosiale sisteme wat pro-sosiale gedrag en kulturele relativisme reflekteer wat vitaliteit in die stedelike ruimte meebring. Sosiale sisteme speel ‘n veelvlakkige rol in die studiegebied. Dit kan stedelike regenerasie moontlik rig in terme van die pro-aktiewe rol in die lok van nuwe sosiale interaksie en die behoud van bestaande sosiale interaksie, die kreatiewe rol in die aanpassing en verandering van die fisiese omgewing ten einde behoeftes aan te spreek en ‘n ondersteunende rol ten einde hulpbronne soos plaaslike kennis, kreatiwiteit, verbondenheid, energie en eienaarskap te ontsluit.
Keywords: Potchefstroom Central Business District; Social systems; Urban planning; Urban regeneration; Qualitative research